Pendidikan Politik Berbasis Desa Wisata:Analisis Kritis Partisipasi Warga dalam Tata Kelola Budaya di Ponorogo - Hertika, Fety Fitriana; Mahardhani, Ardhana Januar; Sulton, Sulton (Universitas Muhammadiyah Ponorogo, 2025)
This research intends to examine the types of political education arising in the culture-driven governance of tourism villages in Ponorogo and to create a more democratic and educational participation framework for overseeing local cultural heritage. Utilizing a qualitative case study approach, information was gathered via detailed interviews, participant observation, and document analysis within tourism villages that oversee Reog cultural sites. The results indicate that tourism villages serve as platforms for political education that enhance citizens' deliberative abilities, legal and civic knowledge, critical understanding of power dynamics, and teamwork skills. Citizen participation exists on various levels, from symbolic to consultative engagement, with cultural organizations and youth groups acting as important links between residents and village officials. Nonetheless, unequal opportunities for participation and the prevalence of certain actors continue to limit the democratization of cultural governance. This research suggests a participatory model for democratic education that includes inclusive deliberative environments, programs for enhancing political skills, mechanisms for social accountability, and the incorporation of local cultural values as the basis for governance. In summary, tourism villages function not just as venues for cultural preservation but also as local democratic experiments that can improve political education when bolstered by transparent and inclusive governance frameworks.